DEVONIAN TRILOBITES FROM THE FALKAND ISLANDS - Pires De Carvalho M.Da.G. (My University, 2006)
New trilobite material is described from the Fox Bay Formation (Lower Devonian; Pragian) of the Falkland Islands (South Atlantic). The fossils were collected from many localities in both East and West Falkland and represent the first significant collection of trilobites from East Falkland. The trilobites belong to three higher taxa: Proetida (the first proetid record in these islands); Homalonotidae, Burmeisteria Salter, 1865; and Calmoniidae, including Bainella Rennie, 1930 and Metacryphaeus Reed, 1907. All of the forms except proetids have now been found in both East and West Falkland. © 2006 The Palaeontological Association.
Keywords: CALMONIIDAE; DEVONIAN; FALKLAND ISLANDS; HOMALONOTIDAE; PROETIDA; SYSTEMATICS; TRILOBITES; Paleozoic::Devonian; Палеозой::Девонская